Size does matter – susceptibility of apple for grey mould is affected by cell size. (7th October 2019) - Naets, M.; Wang, Z.; Verboven, P.; Nicolaï, B.; Keulemans, W.; Geeraerd, A.
Abstract : Apple is a seasonal product that is stored for long periods of time, during which fungal‐caused decay can occur. Previous infection experiments of intact Jonagored apple with Botrytis cinerea displayed apparent differences in lesion expansion rate with respect to inoculation position on the fruit (on, above or below the equator). The goal of this study was to investigate whether these differences are consistent or not and if so, to relate them to fruit characteristics. The study involved measuring the hue angle of the intended inoculation spots prior to inoculation, and firmness and total soluble solids content of fruit from the same batch. Results showed that firmness correlated somewhat (−0.55 and −0.72 for shadow and sun side, respectively) with lesion diameter expansion rate. In a subsequent step, X‐ray imaging was carried out for samples from each position. Analysis of 3D reconstructions by microcomputed tomography of these diffraction images showed that cell size was strongly correlated (0.996) to lesion diameter expansion rate. Finally, it was investigated if cell size could also be used to rank different apple cultivars for their susceptibility to B. cinerea . The result shows that there is a clear distinction between Jonagold and Golden Delicious (non‐blushing variety), which have a smaller cell size, and Braeburn and Kanzi, which have a larger cell size (overall correlation of 0.87). This indicates that cell size may also be an important factor in determining susceptibility across cultivars.